The Herschel SPIRE Fourier Transform Spectrometer Spectral Feature Finder – III. Line identification and off-axis spectra. Issue 4 (13th June 2020) - Benson, Chris S; Hładczuk, N; Spencer, L D; Robb, A; Scott, J; Valtchanov, I; Hopwood, R; Naylor., D A
ABSTRACT: The European Space Agency Herschel Spectral and Photometric Imaging Receiver (SPIRE) Fourier Transform Spectrometer (FTS) Spectral Feature Finder (FF) project is an automated spectral feature fitting routine developed within the SPIRE instrument team to extract all prominent spectral features from all publicly available SPIRE FTS observations. We present the extension of the FF to include the off-axis detectors of the FTS in sparsely sampled single-pointing observations, the results of which have been ingested into the catalogue. We also present the results from an automated routine for identifications of the atomic/molecular transitions that correspond to the spectral features extracted by the FF. We use a template of 307 atomic fine structure and molecular lines that are commonly found in SPIRE FTS spectra for the cross-match. The routine makes use of information provided by the line identification to search for low signal-to-noise ratio features that have been excluded or missed by the iterative FF. In total, the atomic/molecular transitions of 178 942 lines are identified (corresponding to 83 per cent of the entire FF catalogue), and an additional 33 840 spectral lines associated with missing features from SPIRE FTS observations are added to the FF catalogue.